2014
DOI: 10.1080/09168451.2014.905180
|View full text |Cite
|
Sign up to set email alerts
|

Desmodianone H and uncinanone B, potential tyrosinase inhibitors obtained from Lespedeza maximowiczii by using bioactivity-guided isolation

Abstract: A new bioactive compound, namely desmodianone H(1), and another known compound uncinanone B(2) were first isolated using bioactivity-guided isolation from the leaves of Lespedeza maximowiczii and structures were elucidated by comprehensive analysis of their nuclear magnetic resonance and mass spectrometry data. Compounds 1 and 2 exhibited strong inhibitory effects on mushroom tyrosinase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, the following metabolites were detected in the largest quantities in stems 6 months after germination (Figure 2b): amino acids such as valine (2), isoleucine (3), serine (4), threonine (5), aspartic acid (6), and tyrosine (9); sugars such as xylitol (15), myo-inositol (20), and maltose (22); malonic acid (10); palmitic acid (23); and two nonidentified metabolites (26 and 27). The levels of sugars such as fructose (16), glucose (17), and sucrose (21) were higher in stems harvested in November (at 8 months) than in stems harvested during other months.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the following metabolites were detected in the largest quantities in stems 6 months after germination (Figure 2b): amino acids such as valine (2), isoleucine (3), serine (4), threonine (5), aspartic acid (6), and tyrosine (9); sugars such as xylitol (15), myo-inositol (20), and maltose (22); malonic acid (10); palmitic acid (23); and two nonidentified metabolites (26 and 27). The levels of sugars such as fructose (16), glucose (17), and sucrose (21) were higher in stems harvested in November (at 8 months) than in stems harvested during other months.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In the correlation map (Figure 3c,d), four metabolites, isovitexin (38), daidzein (39), desmodianone H (48), and uncinanone B (49), which were strongly positively correlated with each other, were reported to be regulatory agents of melanogenesis. 9,23,24 As these metabolites were present with the largest quantities in samples harvested 6 months after germination, they may be the most active 6 months after germination. The samples at this time were harvested in September, which is the start of the fall season in Korea.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study reported by Heo et al., two new isoflavones desmodianone H and uncinanone B have been identified as novel tyrosinase inhibitors. However, uncinanone B has higher anti-tyrosinase rate than desmodianone H 264 . Glyasperin C from Glycyrrhiza glabra is another kind of isoflavone identified as tyrosinase inhibitor 265 .…”
Section: Inhibitors From Natural Semisynthetic and Synthetic Sourcesmentioning
confidence: 99%
“…Isoflavone glabrene is an inhibitor of both monophenolase and diphenolase to tyrosinase [43]. Two isoflavones, uncinanone B and desmodianone H, inhibit tyrosinase activity, with uncinanone B exhibiting stronger inhibition than desmodianone H [44]. The isoflavones daidzein, glyasperin C, formononetin, genistein, mirkoin, texasin, tectorigenin, and odoratin inhibit tyrosinase activity [45].…”
Section: Competitive Inhibitory Typementioning
confidence: 99%